Raw seawater temperature, conductivity and salinity obtained at different depths by CTD buoy 2019O1 as part of the MOSAiC Distributed Network - Hoppmann, Mario; Kuznetsov, Ivan; Fang, Ying-Chih; Rabe, Benjamin (In: Hoppmann, M et al. (2021): Raw data of CTD buoys 2019O1 to 2019O8 as part of the MOSAiC Distributed Network [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.937271, 2021)
A set of eight ice-tethered buoy systems (2019O1 to 2019O8) were deployed by the Akademik Fedorov in the Northern Laptev Sea in early October 2019 as part of the MOSAiC Distributed Network. Each buoy consisted of 5 Seabird SBE37IMP Microcat CTDs mounted along an inductive modem tether at depths of 10, 20, 50, 75 and 100m. The buoys were installed on stable sea ice floes (designated as “M-sites”) at a distance of 15-35 km around the main MOSAiC ice camp, and co-located with Snow Buoys, Ice Mass Balance Buoys and D-TOP ocean profilers. The individual instruments were programmed to record oceanographic data internally at 2-minute intervals. The surface unit of the buoy prompted the instruments for an additional measurement every 10 minutes, which was then transmitted to a base station via iridium along with GPS position and time, as well as surface temperature. After a several months long drift through the Central Arctic Ocean, 4 out of 8 buoys were recovered in August 2020, and the internally recorded data from the CTDs were secured. The attached zip archive comprises the unprocessed 10-minute data transmitted by buoy 2019O1 (.txt file), as well as the 2-minute data downloaded and converted from the 5 individual CTDs after their recovery (either .cap or .cnv). A processed and quality controlled version of this dataset will be supplemented and linked to upon completion. A link to a data paper describing the processing will be given below.
Keywords: Arctic Ocean; buoy; eddy; mesoscale; MOSAIC_PO; oceanography; Transpolar Drift